Pengaruh Motivasi Kerja dan Kemampuan Kerja Terhadap Kepuasan Kerja Pegawai Pada Dinas Kelautan Perikanan Kabupaten Bima - Faturrahman, Muhammad; Mukhlis, Mukhlis; Kusumayadi, Firmansyah (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the influence of work motivation and work ability on employee job satisfaction at the Department of Marine and Fisheries of Bima Regency. The research employed a quantitative approach with an associative type of study. The population consisted of 67 employees, and a sample of 38 civil servants was selected using a purposive sampling technique. Data were collected through a closed-ended questionnaire using a five-point Likert scale and analyzed using multiple linear regression with SPSS version 26. The validity and reliability tests confirmed that all items were valid and reliable. The results indicate that work motivation has a positive and significant effect on job satisfaction, and work ability also shows a positive and significant impact. Simultaneously, both variables significantly influence job satisfaction with a coefficient of determination (R²) of 0.967, meaning that 96.7% of job satisfaction variation is explained by motivation and work ability. These findings confirm that enhancing employee motivation and competence is a strategic factor in improving job satisfaction and performance in public sector organizations.